Analisis Faktor Syariah terhadap Kinerja Portofolio pada Pelemahan dan Penguatan Nilai Tukar Rupiah - Edryoko Dwi Hardono; Budi Purwanto; Wita Juwita Ermawati (IPB University, 2020)
IHSG and ISSI in the last three periods show that standard deviations have increased and the yield rate has declined. Preliminary observations found that during this period there was a weakening of the Rupiah against the US dollar which was reported to weaken from February to October 2018 and regained strength afterwards. The focus of this research is to analyze the performance of Islamic stock portfolios and general stock portfolios compiled with the Markowitz method under conditions of a weakening exchange rate and when the exchange rate conditions strengthen. The results of the portfolio formation reveal that, more Islamic stocks are needed when the condition of the rupiah exchange rate weakens and fewer Islamic stocks are needed when the exchange rate conditions strengthen. Islamic stock portfolios have returns and risks that are greater than the general portfolio in each condition. However, the performance of the Islamic stock portfolio is inversely proportional to the general stock portfolio.